Communication Model for Community Development of Sharia Bank Financing Products in Empowering Women - Nada Arina Romli; Dini Safitrir; Prima Yustitia Nurul Islami (LPPM Universitas Terbuka, 2023)
This study examines a case study of group entrepreneurial financing products initiated by Islamic Banks by implementing the Grameen Bank program. The concept of the financing product used is a product that provides capital financing and business knowledge to poor women's business groups without collateral. The guarantee used is the trust between group members in Indonesian called Tanggung Renteng or joint responsibility of the whole community. This study aims to determine the community development model that is applied in promoting financial products and to motivate community members to become entrepreneurs. The research method used in this research is a qualitative research method with a case study approach and the concept of social capital Islamic values. In searching for data, researchers conducted semi-structured interviews and passive participant observation. This research was conducted in the female entrepreneur community in Bekasi.The result of this research is community development communication model is carried out in several stages, namely the pre-marketing stage, survey and observation, training, and provision of capital assistance and monitoring. This community development communication model through Grameen Bank to empower women applies the concept of social capital based on Islamic values including the values of the ummah, wahidah, uhuwah, and ta'awun.